If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6T + -9 = 4T + -2T Reorder the terms: -9 + 6T = 4T + -2T Combine like terms: 4T + -2T = 2T -9 + 6T = 2T Solving -9 + 6T = 2T Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '-2T' to each side of the equation. -9 + 6T + -2T = 2T + -2T Combine like terms: 6T + -2T = 4T -9 + 4T = 2T + -2T Combine like terms: 2T + -2T = 0 -9 + 4T = 0 Add '9' to each side of the equation. -9 + 9 + 4T = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 4T = 0 + 9 4T = 0 + 9 Combine like terms: 0 + 9 = 9 4T = 9 Divide each side by '4'. T = 2.25 Simplifying T = 2.25
| 2x^2+6x+3=0 | | 2x+5=13y | | 12x^3-27x^2-27x= | | -28+44= | | 2(x-6)=8 | | 3(3n+4)-2=5(n-1)-9 | | 8x+39=2x-15 | | 13y+5+2x= | | 15*x^3+30*x^2-65x-15=0 | | -3a=-12 | | 8a+5+11=0 | | 7p+15p= | | 5y-13=2 | | 3x+-2=-15 | | 12+6(z-2)=5z+1 | | 13-5y+2x= | | 11y+16z+24z+8y= | | 5x+2=35 | | g(x)=x^3+4x^2+7x+28 | | .8R+1=.08R+1.54 | | -9c-3b+15c= | | -6x=24 | | (-6+3r)+-1(r+4)=-2(r+-4) | | 8x+3-5x= | | 3(r-2)-(r+4)=-2(r-4) | | 4e-16=2e | | 5x+-11=-16 | | 9y-16y=-28-35 | | x^2+10x-32=0 | | 2y-28=42-5y | | .666666666(38-b)=0 | | x^2=28 |